The Effectiveness of Scenario-Based Cybersecurity Day Camps in Southern Rural Appalachia - Anna P. Rodgers-Stine; Tania Williams (Journal of Cybersecurity Education, Research & Practice)
As the emphasis on cybersecurity instruction in the K12 environment continues to expand, furthering access to cybersecurity education is paramount across the United States. While designated cybersecurity courses are not available in many schools, the implementation of cybersecurity camps may help to bridge the gap and increase student interest in and awareness of cybersecurity as a field. From 2021 through 2024, cybersecurity day camps were held in a region in rural southern Appalachia with the goal of increasing student interest and access to cybersecurity topics. Through the creation and implementation of these camps, it was found that scenario-based cybersecurity day camps with a focus on experiential learning were effective in generating student interest and engagement in cybersecurity, with students attending reporting a significant increase in knowledge and interest as a result of the day camps. While the focus of this research is specifically on students in rural southern Appalachia, the findings in the research may create a pathway to assist in the creation and implementation of effective cybersecurity day camps in other regions.